2019
DOI: 10.3389/fgene.2019.00325
|View full text |Cite
|
Sign up to set email alerts
|

The Cord Blood Insulin and Mitochondrial DNA Content Related Methylome

Abstract: Mitochondrial dysfunction seems to play a key role in the etiology of insulin resistance. At birth, a link has already been established between mitochondrial DNA (mtDNA) content and insulin levels in cord blood. In this study, we explore shared epigenetic mechanisms of the association between mtDNA content and insulin levels, supporting the developmental origins of this link. First, the association between cord blood insulin and mtDNA content in 882 newborns of the ENVIR ON AGE birth coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…The generation of important co-substrates required for histone phosphorylation, acetylation and deacetylation processes, such as adenosine triphosphate (ATP), acetyl CoA, flavin adenine dinucleotide, and nicotinamide adenine dinucleotide depends again on mitochondrial activity [ 74 ]. In a study of the ENVIR ON AGE cohort investigating the relationship between epigenome-wide methylation with cord blood insulin and mtDNA content, several pathways and differentially methylated regions (DMRs) also pointed in the direction of histone modification as one of the underlying mechanisms connecting these factors [ 75 ]. Dysfunctions in mitochondrial activity represented by alterations in mtDNA content may, therefore, have direct effects on global DNA methylation profiles [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The generation of important co-substrates required for histone phosphorylation, acetylation and deacetylation processes, such as adenosine triphosphate (ATP), acetyl CoA, flavin adenine dinucleotide, and nicotinamide adenine dinucleotide depends again on mitochondrial activity [ 74 ]. In a study of the ENVIR ON AGE cohort investigating the relationship between epigenome-wide methylation with cord blood insulin and mtDNA content, several pathways and differentially methylated regions (DMRs) also pointed in the direction of histone modification as one of the underlying mechanisms connecting these factors [ 75 ]. Dysfunctions in mitochondrial activity represented by alterations in mtDNA content may, therefore, have direct effects on global DNA methylation profiles [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…[77] Moreover, one association appeared to persist (cg08973675 (SLC25A28)) in a subsequent look-up population of 4-and 8-year-old children. Two recent studies demonstrated 34 significant differentially methylated nDNA regions in relation to cord blood mtDNAcn [90] and an association between mtDNA methylation load and newly discovered mitochondrial peptides [97]. Although no human study appears to have prospectively followed mitochondrial function in individuals from birth to adulthood, mtDNA density is lower at birth in infants exposed to metabolic stress [78,88], positively associates with cord blood insulin [90,96], and is prospectively associated with insulin resistance [102], diabetes onset [26] and cardiovascular disease [25] in adulthood.…”
Section: (Ii) Human Studiesmentioning
confidence: 99%
“…A positive association between metabolic hormones (i.e. leptin and insulin) and mtDNA content in early life has been reported 26,27 . Breast milk contains the hormone leptin, which may reduce psychosocial stress in infants 48 .…”
Section: Discussionmentioning
confidence: 99%
“…A lower mtDNA copy number is a potential biomarker for type 2 diabetes mellitus 24 , while an increased mtDNA copy number is linked with a lower risk of metabolic syndrome in adults 25 . Furthermore, mtDNA content has been positively associated with metabolic hormones such as leptin and insulin in early life 26,27 . In addition, a reduced mtDNA copy number has also been associated with aging [28][29][30] and has been suggested as a biomarker for age-related neurodegenerative diseases, such as Parkinson's disease 31 .…”
mentioning
confidence: 99%